Use of fermented rubber seed (Havea bransiliesis) in diets on growth and survival rate of Nile tilapia BEST (Oreochromis niloticus) fingerlings - Rudy Agam; Indra Suharman; Nur Asiah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted for 56 days from 09 April to 04 June 2015. Theaim of this research was to find out response of Nile tilapia BEST (Oreochromisniloticus) fingerling on the use of fermented rubber seed in diets. The methods usedin this research was an experimental method and Completely randomized design onefactor with 4 treatments. The fish used in this research with size 2,54 - 2,88 gr asmuch as 400 fish. Fish were reared in 1x1x1 m3 in cage with stocking density of20/cage. Feeding trials were replacing with palm kernel cake with rubber seedfermentation applied to 0, 25, 35 and 45% for 25% protein content.The result showed that a diets containing 45% fermented rubber seed mealand 55% palm kernel cake (P3) support a good specific growth rate (3,67%/day), feedefficiency (29.36%) and protein retention (26,54%). Survival rate of fish was high(96,7 – 98,3%). It this concluded that up to 55% palm kernel cake can be substitutedwith fermented rubber sedd meal in the diets for Nile tilapia BEST.Keyword: Oreochromis niloticus, fermented rubber seed, palm kernel cake,substitution, diets